2022
DOI: 10.1097/ypg.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Mendelian randomization in psychiatry: a comprehensive systematic review

Abstract: Psychiatric diseases exact a heavy socioeconomic toll, and it is particularly difficult to identify their risk factors and causative mechanisms due to their multifactorial nature, the limited physiopathological insight, the many confounding factors, and the potential reverse causality between the risk factors and psychiatric diseases. These characteristics make Mendelian randomization (MR) a precious tool for studying these disorders. MR is an analytical method that employs genetic variants linked to a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 103 publications
0
17
0
Order By: Relevance
“…The key research topics, top countries, institutions, journals and authors have been identified. Findings from the present study may be useful in identifying important topics for future research such as screening and diagnosis of at-risk populations based on the polygenic risk score (Fullerton and Nurnberger, 2019), personalised therapeutical options based on biomarkers (Le-Niculescu et al, 2021), and Mendelian randomisation based on genetic associations obtained with GWAS to infer causality between exposures and outcomes (Saccaro et al, 2022). This study should also serve to facilitate collaboration across research groups with similar scientific interests in the field of genetic studies in bipolar disorder.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The key research topics, top countries, institutions, journals and authors have been identified. Findings from the present study may be useful in identifying important topics for future research such as screening and diagnosis of at-risk populations based on the polygenic risk score (Fullerton and Nurnberger, 2019), personalised therapeutical options based on biomarkers (Le-Niculescu et al, 2021), and Mendelian randomisation based on genetic associations obtained with GWAS to infer causality between exposures and outcomes (Saccaro et al, 2022). This study should also serve to facilitate collaboration across research groups with similar scientific interests in the field of genetic studies in bipolar disorder.…”
Section: Discussionmentioning
confidence: 88%
“…Numerous genome-wide association studies (GWAS) have established several loci with a small impact that may account for heritability (Lonergan et al ., 2007; Baum et al ., 2008; Ferreira et al ., 2008; Scott et al ., 2009; Smith et al ., 2009; Cichon et al ., 2011; Psychiatric GWAS Consortium Bipolar Disorder Working Group, 2011; Chen et al ., 2013; Green et al ., 2013; Muhleisen et al ., 2014; Hou et al ., 2016; Stahl et al ., 2019; Mullins et al ., 2021). These include 30 newly discovered loci encoding ion channels, neurotransmitter transporters and synaptic components (Stahl et al ., 2019) and 15 genes robustly linked to bipolar disorder via gene expression, encoding druggable targets such as HTR6, MCHR1, DCLK3 and FURIN (Mullins et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, mendelian randomization studies suggest a causal implication of a proinflammatory status in the risk of developing BD (195,196). Although results about genetic markers of the disorder are still inconclusive, genetic testing of patients has identified polymorphisms associated with mediators of immune response and inflammation, including TNF-α and IL-6, which have been consistently associated with BD and earlier disease onset (197)(198)(199).…”
Section: Inflammatory Markers Sleep and Gut Health: The Effects Of In...mentioning
confidence: 99%
“…Twin-based heritability estimation (Goodrich et al , 2016; Xie et al , 2016) and increasing microbiome genome-wide association study (GWAS) analyses (Kurilshikov et al , 2021; Liu et al , 2021b, 2022; Lopera-Maya et al , 2022; Qin et al , 2022) consistently indicated that host genetics influence the composition of the human gut microbiome and can do so in ways that impact host metabolism. A recent systematic review of MR studies highlighted contradicting findings on the causal effect of the microbiome on schizophrenia (Saccaro et al , 2022). In addition, the classes of gut bacteria identified as risk factors for schizophrenia differ between these two studies [i.e.…”
Section: Introductionmentioning
confidence: 99%